2022
DOI: 10.1111/1759-7714.14594
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the characteristics and survival of patients with non‐small‐cell lung cancer: A retrospective analytical study based on real‐world clinical data of the Korean population

Abstract: Purpose This study aimed to investigate the differences in characteristics, clinical stages, treatment modalities, and survival outcomes in patients with non‐small‐cell lung cancer (NSCLC) based on sex differences using Korean nationwide registry data. Methods We analyzed the data of 8650 patients diagnosed with NSCLC between 2014 and 2017, obtained from the Korean Association for Lung Cancer Registry (KALC‐R). The Cox proportional hazard model was used to define the differences in survival based on sex. Prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Other factors such as advanced stage and sex (male) were found predictive of survival as well. We found sex predictive of OS, in keeping with prior findings [23–26]. We did not find sex predictive of PFS, but literature contradictory to this finding remains scarce.…”
Section: Discussionsupporting
confidence: 91%
“…Other factors such as advanced stage and sex (male) were found predictive of survival as well. We found sex predictive of OS, in keeping with prior findings [23–26]. We did not find sex predictive of PFS, but literature contradictory to this finding remains scarce.…”
Section: Discussionsupporting
confidence: 91%
“…This theory remains speculative within the context of our study, as cortisol measurements were not included in our patient evaluations, In addition to DHEA, sex itself could be a prognostic factor instead of a predictive factor in clinical outcomes in NSCLC. Data from the Korean Association for Lung Cancer Registry showed that male patients with NSCLC had poorer prognoses compared to females after adjusting for clinical variables, and the difference was consistent across stages of diseases [35]. Another comprehensive analysis using Swedish national populationbased registries described the sex difference in NSCLC outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The present study, which included 47 patients, demonstrated pembrolizumab therapy could cause BP. Interestingly, studies have linked irAEs to higher rates of treatment success and improved survival following pembrolizumab therapy (56,57). Furthermore, it has been suggested that the occurrence of irCAEs may be a useful indicator for predicting improved tumor response and better survival among cancer patients receiving ICIs immunotherapy (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have linked irAEs to higher rates of treatment success and improved survival following pembrolizumab therapy (56,57). Furthermore, it has been suggested that the occurrence of irCAEs may be a useful indicator for predicting improved tumor response and better survival among cancer patients receiving ICIs immunotherapy (57,58). However, the effectiveness of irAEs as a predictor was reduced because irAEs occurr ed only afte r IC Is tre atm ent commen ce ment .…”
Section: Discussionmentioning
confidence: 99%